A STUDY OF THE SCIENCE OF I’JAZIL QUR’AN AND ITS FUNCTION IN REVEALING THE SPECIALITY OF THE QUR’AN HOLISTICALLY - Eka Nurhidayat (Journal of Social Science, 2026)
Objective: This study aims to examine the conceptual framework of Iʿjāz al-Qur’an and to explain its function in revealing the distinctiveness of the Qur’an from multiple dimensions, including linguistic, stylistic, structural, scientific, and epistemological aspects. Method: Employing a qualitative-descriptive approach through library research, this study analyzes both classical and contemporary scholarly sources related to ʿUlūm al-Qur’an and Islamic studies. Results: The findings indicate that the science of Iʿjāz al-Qur’an functions not merely as a theological tool for affirming the authenticity of revelation, but also as a methodological framework that enhances a rational and contextual understanding of the Qur’anic message. Through its multidimensional analysis, Iʿjāz al-Qur’an bridges revelation, reason, and empirical reality, thereby maintaining its relevance in addressing contemporary intellectual challenges. Consequently, the science of Iʿjāz al-Qur’an plays a strategic role in strengthening religious faith while simultaneously fostering integrative and dynamic approaches to Qur’anic studies. Novelty: The science of Iʿjāz al-Qur’an constitutes a fundamental discipline within Qur’anic studies that seeks to uncover the unique and inimitable nature of the Qur’an as divine revelation.